HUBUNGAN STRES DENGAN KUALITAS TIDUR MAHASISWA PROFESI KEPERAWATAN STIKes RANAH MINANG PADANG TAHUN 2016 - Wahyuni, Leni Tri (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Stress is the body's response that is not specific to any demands or workload. Some ofthe stress may be experienced by students of the nursing profession, because at thisstage do the nursing profession, professional skills in real situations, displayingprofessional attitudes and behavior. This study aims to determine the relationship ofstress and sleep quality professional students S-1 Nursing STIKes Minang Padang Year2016. This study was analytic sampling technique is total sampling, with a sample sizeof 46 people. The study was conducted on 23 August to 14 September 2016. Data wasanalyzed by univariate and bivariate statistical test by using chi-square with 95%confidence α = 0.05. The result showed 56.5% had moderate stress and poor sleepquality 82.6 with a P value> 0.001. The result showed no relationship between stressand sleep quality professional students S-1 Nursing STIKes Minang Padang in 2016.Expected to educational institutions to provide motivation to professional students sothat the students could face severe stress at the time undergoing professional education.Keywords: Sleep Quality; stress